MODELLING DOMINANT LANGUAGE PEDAGOGICAL PRACTICES TO IMMERSE ARABIC LEARNERS - Saheed Ahmad Rufai (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
The achievements of language pedagogical models have been studied through the use of input-output models. While teaching and learning programmes are the input, learners’ achievements are the output. However, some specific models have been found to be more effective and evaluated more than others. It is noted that of all the components of language pedagogical models, the specific language learning strategies employed have received less attention. This study evaluates four dominant language pedagogical models namely the Alliance Francaise Model (for French), the Goethe Institut Model (for German), Instituto Cervantes Model (for Spanish), and the model the European-funded Pan-European Task-based Activities in Language Learning (PETALL) project which is co-funded by the Lifelong Learning Programme of the European Union. Consequently, the strengths identified are reformulated as principles guiding best language pedagogical practices and translated into curriculum conceptual and design framework for a proposed and tentatively tagged, “The Arabic World”. The ultimate purpose wass to replicate some of such successful outcome-based dominant language pedagogical practices in the context of Modern Standard Arabic.